ANALISIS FAKTOR YANG MEMPENGARUHI HARGA KOPI ARABIKA DI PROVINSI SUMATERA UTARA - Indana Zulfa Batubara; Rahmanta Ginting; Thomson Sebayang (Program Studi Agribisnis, Fakultas Pertanian, Universitas Sumatera Utara, 2018)
The purpose of this research is to analyze the factors that influence the price of arabica coffee in North Sumatera Province. The methods of this research are Engle-Granger Cointegration and Error Correction Model (ECM) method to identify factors that influence the price of arabica coffee in North Sumatera Province in long and short term period of 1992-2016 using Eviews 7.1 application tool. The results showed that the price of arabica coffee in the Province North Sumatra is significantly influenced by the amount of coffee production, the population, the Rupiah exchange rate against the US Dollar, and the world coffee price. In long term, the variable of population and world coffee price have a significant effect on arabica coffee price. While in the short term, only the world coffee price variable significantly influences the price of arabica coffee in the Province North Sumatra. Keywords: Arabica Coffee Price, Coffee Production, Rupiah Exchange Rate, World Coffee Price